The Association Between Combined Oral Contraceptive Use and the Incidence of High-Density Lesions on Digital Mammography - Carissa Faustina; Nina ISH Supit; Nungky Kusumaningtyas; Alvin Setiawan; Ratna Sari Wijaya (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: High mammographic density (MD) is an independent breast cancer risk factor that hinders early detection through the